Aligning Three Substance Use Disorder Interventions among a Tribe in the Southwest United States: Pilot Feasibility for Cultural Re-Centering, Dissemination, and Implementation - Hirchak, Katherine A. (J Ethn Subst Abuse, 2020)
In this article we describe cultural re-centering, dissemination, and implementation activities in partnership between an American Indian reservation community and a university in the Southwest United States. We offer examples of cultural adaptation and implementation of evidence-based treatments (e.g., Motivational Interviewing, Community Reinforcement Approach and the Community Reinforcement and Family Training) using the Interactive Systems Framework. Facilitators and barriers are described within each study including recruitment strategies, training, and sustainability of counselors in the community. Through this Tribal-university partnership, we offer insight on the cultural adaptation and implementation process that will be translatable and clinically meaningful to other rural and reservation communities.